Beneficiamento da castanha de caju: experiências das mulheres da agrovila Sergipe (Serra do Mel/RN) - Silva, Núbia Rosendo da (Universidade Federal Rural do Semi-Árido, 2021)
This research aims to analyze the experiences of women who work with cashew nut processing in Agrovila Sergipe (Serra do Mel/RN). To achieve the main objective, the research specifically proposes: (I) Problematize the work relationships experienced by women from Agrovila Sergipe (Serra do Mel/RN) in the processing of cashew nuts; (II) Discuss the representations of gender roles for women who work with cashew nut processing; (III) Analyze public policies and their resonances in the lives of female collaborators. To strengthen the work and dialogue with the field research, the work dialogues with the authors Soihet and Maria Pedro (2007), Matos (1998), Faria (2009), Saffioti (1987) and others who discussed about the concept of gender and the history of women; about the history of Serra do Mel, and the processing of chestnuts, we dialogued with Lima (2003), Duarte (2019) and etc.: according to the discussions on labor relations, Marx (2012), Ribeiro (1999), Sento- Sé (2000); on public policies, Moraes and Mazzioni (2017), Lambertucci (2009), Höfling (2001). On qualitative research and oral history, we rely on Freitas (2006), Bom Meihy (1996), Alburquerque Jr. (2007; 2006), Gil (2008) and Sá-Silva, et al. (2010). Regarding field research, it took place through semi-structured interviews, in the interviewees' homes, using a recorder. Our web of collaborators was formed by three women with experience in working with cashew nut processing, of different ages, all of whom have lived at Agrovila Sergipe for several years, with whom we conducted semi-structured interviews. From this research, it was possible to conclude that the work with cashew nut processing is also marked by prejudice and health risks. In addition, we found that employment relationships are precarious and without legalizing the rights of female workers, who face several challenges due to the fact that they are women, with a strenuous routine of tasks, and maintenance of household chores as their sole responsibility. Furthermore, the research highlighted the importance of public policies so that the interviewees had access to improvements in the processing of Brazil nuts, in their lives and that of their families.
Keywords: Beneficiamento da castanha de caju; Mulheres; Agrovila Sergipe; Serra do Mel; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL